The Influence of Socioeconomic Factors on Maternal Health Promotion Strategies in Rural Pekalongan District, Central Java - Suparni, Suparni; Ersila, Wahyu; Isyti’aroh, Isyti’aroh; Aisyah, Risqi Dewi; Khuzaiyah, Siti; Andrianirina, Rhino (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2026)
Background: In 2020, Indonesia’s maternal mortality rate (MMR) was 189 per 100,000 live births, well above the SDGs target of 70. High-risk pregnancies significantly contribute to maternal deaths, especially in rural areas with socioeconomic challenges. Disparities in education, income, and healthcare access influence pregnant women’s health-seeking behaviors. ObjectiveThis study aimed to examine the relationship between socioeconomic determinants and pregnancy risk and to develop an evidence-based, community-focused health promotion model that addresses these socioeconomic factors in rural settings. Methods: A cross-sectional study involved 130 pregnant women in the Puskesmas Tirto 1 area, Pekalongan Regency, Central Java. Data collection used structured questionnaires, analyzed via binary logistic regression. A theoretical framework guided community-based health promotion recommendations. Results:  The analysis revealed that age, parity, education, and income collectively affected pregnancy risk (p=0.033). Individually, only income had a significant effect (p=0.039; Exp(B)=0.380; 95% CI: 0.150–0.962), indicating higher income reduces high-risk pregnancy likelihood. Age, parity, and education were not significant predictors. Conclusion: Economic factors are the strongest predictors of pregnancy risk among the variables studied. Maternal health programs in rural areas should incorporate socioeconomic-based strategies through community empowerment, improved healthcare access, and targeted health education.